Mechanisms of LPS-Induced Acute Kidney Injury in Neonatal and Adult Rats - Egor Y. Plotnikov; Anna A. Brezgunova; Irina B. Pevzner; Ljubava D. Zorova; Vasily N. Manskikh; Vasily A. Popkov; Denis N. Silachev; Dmitry B. Zorov (MDPI AG, 2018)
Neonatal sepsis is one of the major causes of mortality and morbidity in newborns, greatly associated with severe acute kidney injury (AKI) and failure. Handling of newborns with kidney damage can be significantly different compared to adults, and it is necessary to consider the individuality of an organism’s response to systemic inflammation. In this study, we used lipopolysaccharide (LPS)-mediated acute kidney injury model to study mechanisms of kidney cells damage in neonatal and adult rats. We found LPS-associated oxidative stress was more severe in adults compared to neonates, as judged by levels of carbonylated proteins and products of lipids peroxidation. In both models, LPS-mediated septic simulation caused apoptosis of kidney cells, albeit to a different degree. Elevated levels of proliferating cell nuclear antigen (PCNA) in the kidney dropped after LPS administration in neonates but increased in adults. Renal fibrosis, as estimated by smooth muscle actin levels, was significantly higher in adult kidneys, whereas these changes were less profound in LPS-treated neonatal kidneys. We concluded that in LPS-mediated AKI model, renal cells of neonatal rats were more tolerant to oxidative stress and suffered less from long-term pathological consequences, such as fibrosis. In addition, we assume that by some features LPS administration simulates the conditions of accelerated aging.